2002
DOI: 10.1155/2002/797934
|View full text |Cite
|
Sign up to set email alerts
|

Brunner’s Gland Hamartoma: A Rare Cause of Gastrointestinal Bleeding – Case Report and Review of the Literature

Abstract: An unusual cause of upper gastrointestinal bleeding is described in a previously healthy 45-year-old man who was admitted to hospital with weakness and fatigue, and had experienced an episode of melena two days before admission. His medical and surgical history was unremarkable. Upon admission to hospital, he showed evidence of iron-deficiency anemia, with a hemoglobin concentration of 61 g/L (normal range 135 to 175 g/L), a mean corpuscular volume of 73 fL (normal range 85.0 to 95.0 fL) and a ferritin concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
(12 reference statements)
0
9
0
4
Order By: Relevance
“…This mostly concerns the hamartomas that are large in size and symptomatic. Symptomatic cases most often present with gastrointestinal bleeding or obstructive symptoms [1, 2, 6, 7, 9, 1214]. In rare cases, Brunner's gland hamartomas have been reported to cause duodenal intussusception [15, 16], “idiopathic” pancreatitis by intermittent obstruction of the Ampulla of Vater [17, 18], and mimicking of pancreatic or duodenal malignancy [15, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mostly concerns the hamartomas that are large in size and symptomatic. Symptomatic cases most often present with gastrointestinal bleeding or obstructive symptoms [1, 2, 6, 7, 9, 1214]. In rare cases, Brunner's gland hamartomas have been reported to cause duodenal intussusception [15, 16], “idiopathic” pancreatitis by intermittent obstruction of the Ampulla of Vater [17, 18], and mimicking of pancreatic or duodenal malignancy [15, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…A previously documented case of severe anemia due to Brunner's gland hamartoma was reported to present with similar symptoms of lightheadedness and melena and a hemoglobin level of 61 g/L (3.8 mmol/L). This case also required erythrocyte concentrate transfusions and as the size was relatively small (3 cm) a segmental duodenal resection was performed [7]. …”
Section: Case Reportmentioning
confidence: 99%
“…Moreover, Brunner's gland hyperplasia may be detected on transabdominal US as a lesion with a heterogeneous echotexture because of multiple small cysts (27). Only a few reports have described the various CT findings of Brunner's gland hyperplasia, including findings of a homogeneously-enhancing mass or of a heterogeneous and hypoattenuating mass with contrast administration (28, 29). In our study, CT revealed a solitary cystic lesion with mild wall enhancement (Fig.…”
Section: Miscellaneous Lesionsmentioning
confidence: 99%
“…Pathologic changes of Brunner glands have also been classified into three types by Feyrter: diffuse nodular hyperplasia throughout the duodenum (type 1), circumscribed nodular hyperplasia limited to the duodenal bulb (type 2), and glandular adenoma with polypoid tumorlike dimensions (type 3) (2,4). It has been suggested that the term Brunner's gland hamartoma is better than Brunner's gland adenoma because of (a) the absence of dysplasia; (b) the lack of encapsulation; and (c) the admixture of tissues-including ducts, acini, smooth muscle tissue, adipose tissue, lymphoid tissue, and Brunner glands-within a single pathologic lesion (4).…”
Section: Discussionmentioning
confidence: 99%